378 Characterizing Functional Genetic Regulatory Elements in Sheep Reference Genome. (21st September 2022) - Murdoch, Brenda M; Davenport, Kimberly M; Xie, Shangqian; Salavati, Mazdak; Clark, Emily; Archibald, Alan; White, Stephen N; Mousel, Michelle R; Worley, Kim; Bhattarai, Suraj; McKay, Stephanie D; Caulton, Alex; et al.
Abstract: Characterizing the locations of genetic regulatory elements is critical for understanding the regulatory mechanisms of complex phenotypic traits related to production traits and health in livestock species. The Ovine Functional Annotation of Animal Genomes (FAANG) Project aims to characterize transcriptional regulatory elements across the sheep genome to facilitate a better understanding of the biological mechanisms influencing phenotypic traits in sheep. Assays including sequencing of messenger RNA (mRNA-seq), cap analysis of gene expression (CAGE), chromatin immunoprecipitation of histones (ChIP-seq), assay for transposase-accessible chromatin (ATAC-seq), whole genome bisulfite sequencing (WGBS) and reduced representation bisulfite sequencing (RRBS) were performed on tissues collected from the Rambouillet ewe used to assemble the reference genome ARS-UI_Ramb_v2.0. Histone modifications were used to define nine chromatin states for tissues across the genome depicting promoters and enhancers (active, poised, and repressed) using ChromHMM. Chromatin states were overlayed with RNA-seq, ATAC-seq and DNA methylation. These data suggest that active promoter and enhancer states reside in open chromatin regions with a greater transcriptional activity and hypomethylated regions than other states. Further, poised and repressed enhancers did not primarily reside in open chromatin and had less transcriptional activity and more hypermethylated sites compared with active states. Collectively these data define transcriptional regulatory regions throughout the ovine genome which provides a valuable resource to better understand regulatory regions in the genome and how these influence economically important traits in sheep and other livestock species.